Trade unions in Malaysia: Perspectives of employers & employees of unionized companies. - Che Rose, Raduan; Kumar, Naresh; Ramasamy, Nagiah (Shri Ram Centre, 2011)
This paper examines the views of employees and employers from unionised companies on trade unions in Peninsular Malaysia. A majority of nonunion members perceived that employers do not display a positive attitude towards the unions at workplace. The role of the individual rather than the collective aspirations of employees is clearly emphasised by employers. The high level of employers’ opposition to unionisation is clearly an indicator of its role in the erosion of collective representation, leading to the diminution of union organising efforts. The highly competitive and dynamic globalized business environment has been the key driver in employers’ attitudes towards trade unions. Trade unions need to review their organising strategies, as well as their internal procedures and processes. Trade unions should go beyond their traditional roles and engage in activities strategic to their communities and employers.